Case Report: Term Birth with Unknown Intrauterine Device (IUD) in Situ - Melisa Indah Mustikasari; Aditya Fendi Uji Pamungkas; Razita Aulia Azkia; Made Chindy Dwiyanti Marheni Putri; I Made Ananta Wiguna (Health Dynamics, 2025)
Intrauterine contraceptive devices (IUDs) are highly efficient at preventing unintended pregnancies, without minimal failure rates, rare complications such as retention or displacement during pregnancy may lead to significant clinical challenge. This case discusses the diagnostic and management challenges of presumed IUD retention in the background of poor antenatal care. Multigravida woman, GIII/PII/A0, 24 years old with two previous caesarean deliveries, admitted in active labor at term. She received no antenatal care for her pregnancy because she could not afford it, and she thought that, because she had an IUD placed after her last cesarean section, she was infertile. On examination, uterine fundal height was 34 cm, amniotic membranes were intact, and the cervix was fully dilated as labor progressed. Spontaneous vaginal delivery was achieved and a 4050-gram (9 lb) neonate was delivered with Apgar scores of 4 at one minute and 5 at five minutes. In the postpartum period, she experienced complications including retained placenta requiring manual extraction and an estimated blood loss of 250 mL. After complete exploration and subsequent imaging, the IUD was not visualized, suggesting either early expulsion, unnoticed displacement or misplacement occurred at insertion. The patient’s postpartum course was unremarkable with appropriate uterotonic therapy and close observation. This case highlights the need for full antenatal care to prevent and manage complications associated with IUDs including displacement or retention that may result in adverse maternal and fetal outcomes. Timely diagnosis and early interventions coupled with appropriate imaging and clinical follow-up services are essential to optimize outcomes and minimize associated risks.